The Impact of Online Customer Reviews (OCRs) On Consumer Purchasing Decision - Ibrahim, Marwa Mahmoud; Mamdouh, Hebat Allah (The Arab Journal of Administration, 2025)
This paper investigates how online customer reviews (OCRs) can affect consumer purchasing decisions mediated by online reviews type and moderated by different demographics. The online customer reviews in this study is measured by valence (ranged from positive to negative), volume (many or few), recentness (whether the online review is recent or old), and the review length (long or short review). Moving to the mediating variable, the online review type is either (objective or subjective) and moderated by demographics (age, gender, income, and education). It’s important to note that there is no sufficient data regarding the effect of online customer reviews (OCRs) on consumer purchasing decisions in Egypt. Hence, this research can contribute to a deeper understanding of (OCRs), this is also necessary for developing valuable indications for the online platforms to enhance their services introduced to the Egyptian market. The current research is based on quantitative data derived from an online survey which was distributed among online users in Egypt. In this sense, the usefulness of this research is that it allows underlining significant issues and formulating vital findings: the online reviews dimensions showed a meaningful relationship between it and between the online purchasing decisions which emphasized the importance of the online customer reviews. Also, other dimensions indicated an effect on the consumer purchasing decision mediated by the online review type, whether it was subjective or objective review. On the other hand, demographics, education, job, and income moderated the relationship between dimensions of online customer reviews and consumer purchasing decisions.